2018
DOI: 10.1177/0969733018792738
|View full text |Cite
|
Sign up to set email alerts
|

The relationship amongst ethical position, religiosity and self-identified culture in student nurses

Abstract: Background/purpose: Research from other disciplines demonstrates that ethical position, idealism, or relativism predicts ethical decision-making. Individuals from diverse cultures ascribe to various religious beliefs and studies have found that religiosity and culture affect ethical decision-making. Moreover, little literature exists regarding undergraduate nursing students’ ethical position; no studies have been conducted in the United States on students’ ethical position, their self-identified culture, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 48 publications
0
14
0
6
Order By: Relevance
“…Unlike studies in other social and health science disciplines, 38 studies in nursing education seldom extend their classification of nursing students’ ethical ideology according to Forsyth’s 43 taxonomy. 52,61 In this current study, a classification of nursing students’ ethical ideologies is provided. Most students were classified as ‘situationists’ on a measure of ethical ideology and were more idealistic than relativistic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike studies in other social and health science disciplines, 38 studies in nursing education seldom extend their classification of nursing students’ ethical ideology according to Forsyth’s 43 taxonomy. 52,61 In this current study, a classification of nursing students’ ethical ideologies is provided. Most students were classified as ‘situationists’ on a measure of ethical ideology and were more idealistic than relativistic.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined ethical ideologies among nursing students. A study by White et al 52 shows that ethical ideologies were associated with self-identified culture, religion and intrinsic religiosity. Smith 53 identified that nursing students at the beginning of their programme start out to be idealistic, but as they progress through their programme and become more disillusioned, cynical and preoccupied with getting through the work, arrived at the end with a loss of idealism, which has implication for caring in nursing.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In nursing students, ethical ideology is associated with professional values (Arries, 2019) self-identified culture, and intrinsic religiosity (White et al, 2019). In their study, White et al (2019) found that students whose parents were not born in the United States scored higher on ethical idealism. Also, if English is not their primary language spoken at home, students scored higher on ethical idealism and relativism, suggesting a cultural link between ethical ideology, language, and birthplace.…”
Section: Overview Of Literature On Moral Philosophy and Ethical Ideology In Nursingmentioning
confidence: 99%
“…Moral performance and decision-making of the nurses can be affected by personal values, and economic, cultural, and environmental conditions. 2,27 For instance, the personal culture or even the organizational culture can hinder nurses from presenting the alternative treatment methods in the hospital. 1 Further attention should be paid to enhancing patients’ understanding regarding the authority to give informed consent for surgery, particularly in clinical settings, such as Iran, in which patients have diverse cultures and beliefs.…”
Section: Discussionmentioning
confidence: 99%